PROGRAM BIMBINGAN KARIER UNTUK MENGEMBANGKAN IDENTITAS KARIER SISWA SMK - Siska Widia Monika; Andi Kiswanto (Bimbingan dan Konseling, FKIP, Universitas Nahdlatul Ulama Cirebon, 2019)
The problems and obstacles experienced by Vocational High School (SMK) students in the academic field are not only about the lack of information about the world of work or higher education, but students do not yet have a clear picture of their abilities, interests, and goals. The purpose of this study was to develop career identity through career guidance programs.This study uses the Pre Experimental Desaign research method. This study uses desaign pre-test and post-test one group design research. Based on the results of the study, it was found that the Effective Career Guidance Program for Developing Career Identity of Class XI Students of SMK 1 Lemahabang.